Twinkle Kids Land Sdn Bhd / Intan Zalina Zakaria ... [et. al] - Zakaria, Intan Zalina; Mohd Mukhtar, Marziah; Mazilan, Mazlida; Subri, Nor Fariza; Ghazali, Rosmalinda (Faculty of Artistic and Creative Technology, 2003)
The importance of early years learning to a child's academic and social development is undeniable. Pre- school years are an ideal time to begin building good foundation for lifelong learning. The skills that children gain in their pre-school years are often the building blocks for their future education and their life. Children who are enrolled in high quality education programmes show higher verbal and intellectual development during early childhood than those who do not. Prior to this, we agree to open a business which offers pre-school education for children from age 4 to 6 years old. Our curriculum recognizes the potential in each child and develops programmes and activities that promote their physical and emotional growth, academic achievement, social relationship and cognitive realms, thus developing the whole child. The curriculum at our child enrichment centre includes lessons in language arts, mathematics, problem solving activities and musics. Our language arts activities include reading aloud, beginning phonic activities, telling and retelling stories and writing. In addition to academic development, activities to develop social and interpersonal skills and emotional maturity are also part and parcel of what we offer to teach self-control, organization, respect, unselfishness and kindness to kids at young age.This is to ensure that children get a rounded education.This is call R.E.A.L ( Results Enhancing & Active Learning Education).